2016
DOI: 10.1007/s12928-016-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radial, brachial, and femoral accesses using hemostatic devices for percutaneous coronary intervention

Abstract: Some studies have suggested that radial access (RA) for percutaneous coronary intervention (PCI) reduces vascular complications and bleeding compared to femoral access (FA). The purpose of this study was to investigate the routine use of hemostatic devices and bleeding complications among RA, brachial access (BA), and FA. Between January 2015 and December 2015, 298 patients treated for PCI with RA were compared with 158 patients using BA and 206 patients using FA. The radial sheath was routinely removed with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
13
2
Order By: Relevance
“…Additionally, in our research, the BA was associated with the highest risk of a puncture site hematoma, which occurred in 23% of patients. In comparison to other studies, hematomas also occurred most commonly in the BA group or were a frequent complication related to the BA, nevertheless, it was generally less common in previous reports compared to the present study, ranging from 1% to 14% [ 7 , 8 , 17 , 18 ]. According to Otsuka et al [ 17 ], pseudoaneurysm was also most common in the BA group (1.3%) versus the RA or FA groups, which was also observed in our study (1.9%), although the respective difference did not reach statistical significance, presumably owing to the number of study subjects.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Additionally, in our research, the BA was associated with the highest risk of a puncture site hematoma, which occurred in 23% of patients. In comparison to other studies, hematomas also occurred most commonly in the BA group or were a frequent complication related to the BA, nevertheless, it was generally less common in previous reports compared to the present study, ranging from 1% to 14% [ 7 , 8 , 17 , 18 ]. According to Otsuka et al [ 17 ], pseudoaneurysm was also most common in the BA group (1.3%) versus the RA or FA groups, which was also observed in our study (1.9%), although the respective difference did not reach statistical significance, presumably owing to the number of study subjects.…”
Section: Discussioncontrasting
confidence: 94%
“…In comparison to other studies, hematomas also occurred most commonly in the BA group or were a frequent complication related to the BA, nevertheless, it was generally less common in previous reports compared to the present study, ranging from 1% to 14% [ 7 , 8 , 17 , 18 ]. According to Otsuka et al [ 17 ], pseudoaneurysm was also most common in the BA group (1.3%) versus the RA or FA groups, which was also observed in our study (1.9%), although the respective difference did not reach statistical significance, presumably owing to the number of study subjects. Although often mentioned as a complication of BA interventions [ 7 , 8 , 19 ], brachial artery thrombosis did not occur in any of the cases in our study.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…3 However, subcutaneous bleeding from arteriovenous fistula (AVF) cannulation that compromise skin and tissue perfusion is rarely reported. 4 A 69-year-old woman with end-stage renal disease, who has undergone hemodialysis via her left wrist radiocephalic AVF, came to our hospital with a painful swelling and blister on her left forearm after a brief episode of dialysis needle dislodgment due to a heavy cough. The dialysis session was immediately stopped.…”
Section: Fundingmentioning
confidence: 99%
“…Indeed, in a study comparing radial and brachial approaches, it has been demonstrated that the latter is associated with an increased formation of hematomas and pseudoaneurysm and a greater procedure duration, fluoroscopy time, and total radiation dose. 4 However, radial access for peripheral intervention has some limitations needed to be discussed. First, the smaller vessel diameter.…”
mentioning
confidence: 99%